Trauma brain injury in paediatric mild blunt head trauma in Hospital Universiti Universiti Sains Malaysia - Song, Cheng Hee (2017)
Background: Paediatric minor head injury is a common presentation in emergency department worldwide. There is controversy about which patients should undergo computed tomography (CT) of the brain. The purpose of our study was to identify the predictors for paediatric traumatic brain injury on CT scan in our population. We also aimed to determine the association between isolated versus non-isolated vomiting with traumatic brain injury on CT brain. Methods: Children with minor head injury (GCS 13-15) presented to Hospital Universiti Sains Malaysia (USM) during the period from 2009 to 2013 were retrospectively reviewed. We evaluated clinical variables such as the mechanism of injury, presenting symptoms and physical signs on the examination for positive traumatic brain injury as determined by CT brain. The data was analysed by chi-square test, simple and multiple logistic regression analyses.Results: A total of 274 patients were enrolled into our study. The mean and standard deviation age of study group was 11.2 (5.39) years old. Traumatic brain injury on CT scan occurred in 49.3% of patients. On multivariable analysis, we identified the following three predictors which were statistically significant: headache (adjusted OR 2.24, 95% CI 1.24, 4.05, p=0.008), giddiness (adjusted OR 3.08, 95% CI 1.27, 7.51, p=0.013) and presence of scalp hematoma (adjusted OR 2.93, 95% CI 1.60, 5.34, p<0.001). TBI on CT scan occurred in 2 of 24 patients in the isolated vomiting group versus 71 of 123 in the non-isolated vomiting group. We found significant association between isolated versus non-isolated vomiting with traumatic brain injury on CT brain (p<0.001). Conclusions: Headache, giddiness and presence of scalp hematoma are independent predictors for minor blunt head injury in our pediatric population. CT brain should be seriously considered in children presenting with vomiting accompanied by othersymptoms and signs suggestive of traumatic brain injury.